Analisis Faktor yang Mempengaruhi Perilaku Pembelian Konsumen terhadap Produk Fajwa Bakery di Bangkinang - Yedi Sispurwanto; Rahmad Akbar (Politeknik Kampar, 2025)
This study aims to examine the extent to which various factors—such as product quality, service, income level, price, consumer preferences, and ease of access to location—affect purchasing decisions for Fajwa Bakery products in Bangkinang. The research method used is a survey, with data collected through direct interviews and field observations. The respondents are customers who have previously purchased Fajwa Bakery products, selected using the accidental sampling technique, based on whoever was encountered and willing to participate. The sample size in this study was determined to be 100 people using the Lemeshow formula. Data analysis was conducted using descriptive methods and multiple linear regression. The results show that most respondents are aged between 20 and 35 years old, female, with a senior high school education level, earn between Rp 1,000,000 and Rp 2,000,000 per month, and have purchased Fajwa Bakery products at least three times in the past year.